The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/app.11315
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the photodegradation of polarized UV‐exposed PMDA–ODA polyimide films

Abstract: Polarized Fourier transform infrared (FTIR) and ultraviolet-visible (UV-VIS) spectroscopy were used to investigate the photodegradation direction of polarized UV (PUV)-irradiated polyimide (PI) films based on pyromellitic dianhydride (PMDA) and 4,4Ј-oxydianiline (ODA). PI films strongly absorb below 350 nm, resulting in a photochemical reaction of the PI. PUV irradiation of the PI film caused a decrease of all existing peaks and formation of new peaks at 3258, 1748, and 1710 cm Ϫ1 in the IR, due to degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…38 Band at 1243 cm Ϫ1 was assigned to ArOOOAr asymmetrical stretching. [39][40][41] The decrease in this band for membranes containing BMI was due to the absence of ether group in BMI. Band at 1080 cm Ϫ1 was assigned to ArOOOAr symmetrical stretching.…”
Section: Chemical Structure Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…38 Band at 1243 cm Ϫ1 was assigned to ArOOOAr asymmetrical stretching. [39][40][41] The decrease in this band for membranes containing BMI was due to the absence of ether group in BMI. Band at 1080 cm Ϫ1 was assigned to ArOOOAr symmetrical stretching.…”
Section: Chemical Structure Analysismentioning
confidence: 92%
“…57,58 The band at 3258 cm Ϫ1 might be assigned to OOH of the OCOOH groups and other OOH groups. 40 The band around 3400 cm Ϫ1 was assigned to OH stretching of coordinated water or alcohol. 58 This might indicate that amic acid caused to incorporate a small amount of complexed NMP as might be described by Scheme 3 and possible alcohol or water was the reason for increase in the band intensity of PSF-BMI-EtOH-L compared to PSF-BMI-EtOH-S within the 3090 -4000 cm Ϫ1 range.…”
Section: Chemical Structure Analysismentioning
confidence: 99%
“…Meanwhile, Schadat et al observed LC photo alignment on coumarin-containing polymers layers [2]. Ha et al and Shitomi et al reported that the photo alignment of polyimide films, including alicyclic and aromatic compounds, depended on the wavelength of the exposure photon [3,4]. However, these polymer materials have low heat resistance, low optical transparency, and are dark brown or yellowish brown.…”
Section: Introductionmentioning
confidence: 99%
“…More and more researcher accept that the method of vacuum deposition provides for a greater degree of purity in the thin film production, opportunity for controlling and computerizing the processes of heating, imidazion and layer formation designed for obtaining standard PI or nanocomposite products of reproducible composition, thickness, structure and properties [12,14]. In figure 3 are compared the spectra of PAA and solid imidization film of PAA to PI obtained after thermal treatment.…”
Section: Vapour Deposition and Solid State Reactionmentioning
confidence: 99%
“…Our studies have focused primarily on vapour deposition of precursors and solid state imidization reaction [7,10,11,12]. Vapour deposition processes of organic layers play an important role in polytronics.…”
Section: Vapour Deposition and Solid State Reactionmentioning
confidence: 99%